Possible routes of SARS‐CoV‐2 invasion in brain: In context of neurological symptoms in COVID‐19 patients. Issue 12 (31st August 2020) - Kumar, Ashutosh; Pareek, Vikas; Prasoon, Pranav; Faiq, Muneeb A.; Kumar, Pavan; Kumari, Chiman; Narayan, Ravi K.
Abstract: Manifestation of neurological symptoms in certain patients of coronavirus disease‐2019 (COVID‐19) has warranted for their virus‐induced etiogenesis. SARS‐CoV‐2, the causative agent of COVID‐19, belongs to the genus of betacoronaviruses which also includes SARS‐CoV‐1 and MERS‐CoV; causative agents for severe acute respiratory syndrome (SARS) in 2002 and Middle East respiratory syndrome (MERS) in 2012, respectively. Studies demonstrating the neural invasion of SARS‐CoV‐2 in vivo are still scarce, although such characteristics of certain other betacoronaviruses are well demonstrated in the literature. Based on the recent evidence for the presence of SARS‐CoV‐2 host cell entry receptors in specific components of the human nervous and vascular tissue, a neural (olfactory and/or vagal), and a hematogenous—crossing the blood–brain barrier, routes have been proposed. The neurological symptoms in COVID‐19 may also arise as a consequence of the "cytokine storm" (characteristically present in severe disease) induced neuroinflammation, or co‐morbidities. There is also a possibility that, there may be multiple routes of SARS‐CoV‐2 entry into the brain, or multiple mechanisms can be involved in the pathogenesis of the neurological symptoms. In this review article, we have discussed the possible routes of SARS‐CoV‐2 brain entry based on the emerging evidence for this virus, and that available for other betacoronaviruses in literature.